Best Practices in Research and Proposal Development- Zinnov’s Way – A Case Study - Sharma, Kshitiz; Vaishnav, Shail Nayankumar (Ushus Journal of Business Management, 2021)
The case is intended to be used as a basis for classroom discussion rather than to illustrate either effective or ineffective handling of a management situation. The case has been written on the basis of generalized experience.This case, based on Zinnov, specifically deals with Research domain. The information on actual research practices is scarcely available in business colleges. Similarly the development of research proposal is extremely important learning topic for future researchers. The case highlights these two aspects in research. The work ensures originality.